2020
DOI: 10.1111/jocd.13739
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscopy as an evaluation method for alopecia areata treatment: A comparative study

Abstract: Alopecia areata (AA) is an extremely common form of nonscarring hair loss, with a calculated lifetime risk of 2%. It affects both sexes and has no racial predilection, and it represents a significant healthcare burden. 1 Despite the high prevalence, there are no evidence-based treatments for AA. 2 Recent research has uncovered new insights into the etiopathogenesis of AA, which opened the door to the development of new treatment options. 3 Lacarrubba and colleagues first described the trichoscopic features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…One study found that final severity of alopecia tool (SALT) score showed significant lower levels in both groups compared to baseline levels (P = 0.025 and P = 0.008) with no significant difference between both treatment modalities in term of clinical improvement, while final alopecia areata symptom impact scale (AASIS) showed significant decrease in PRP group (P = 0.006) but not in triamcinolone group (P = 0.062). 62 Similar results were found in the other study by showing that there was no statistically significant difference in SALT score reduction and hair regrowth scale between these two groups. 63…”
Section: Use Of Platelet Rich Plasma In Hair Disorderssupporting
confidence: 89%
See 1 more Smart Citation
“…One study found that final severity of alopecia tool (SALT) score showed significant lower levels in both groups compared to baseline levels (P = 0.025 and P = 0.008) with no significant difference between both treatment modalities in term of clinical improvement, while final alopecia areata symptom impact scale (AASIS) showed significant decrease in PRP group (P = 0.006) but not in triamcinolone group (P = 0.062). 62 Similar results were found in the other study by showing that there was no statistically significant difference in SALT score reduction and hair regrowth scale between these two groups. 63…”
Section: Use Of Platelet Rich Plasma In Hair Disorderssupporting
confidence: 89%
“… 61 Collectively, many randomized controlled trials demonstrated that treatment with PRP can stimulate hair regrowth to the same extent as intralesional injection of triamcinolone acetonide in the treatment of AA. 62–65 Two recent studies compared the therapeutic effect of intralesional injections of PRP with triamcinolone acetonide in AA. One study found that final severity of alopecia tool (SALT) score showed significant lower levels in both groups compared to baseline levels (P = 0.025 and P = 0.008) with no significant difference between both treatment modalities in term of clinical improvement, while final alopecia areata symptom impact scale (AASIS) showed significant decrease in PRP group (P = 0.006) but not in triamcinolone group (P = 0.062).…”
Section: Use Of Platelet Rich Plasma In Hair Disordersmentioning
confidence: 99%
“…In literature there are few clinical trials discussing treatment of AA with PRP [9], [16], [17], [18], [19], [20], [21], [22], [23], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35] and most of them agree with our results. On the other hand, D'Ovidio and Roberto in 2014 showed restricted usefulness of PRP in long standing cases (more than 2 years) and proposed that PRP effect may be held in reserve for mild cases [44].…”
Section: Discussionsupporting
confidence: 91%
“…These GFs are believed to stimulate stem cells sited in HF at the bulge areas leading to growth of fresh follicles and enhancing angiogenesis [13], [15]. Despite of its promising results in AA, a paucity of randomized controlled clinical trials had been published to assess the efficiency of PRP in management of AA [9], [13], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], 29], [30], [31], [32], [33], [34], [35]. Photobiomodulation (PBM), or low-level laser (or) light therapy (LLLT) is using red light (600-700 nm) or near infrared (700 nm-1000+nm) which is obtained from 5 to 500 mW light-emitting diode (LED) source [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…6 To our knowledge, there are only two other interventional trials that have reported AASIS data, but these studies did not report correlations with SALT scores. 11,12 The mean improvements in AASIS scores observed in the active treatment groups at week 24 ranged from À0.3 to À3.7 on the 0-10 point AASIS scoring system. The AASIS items with the greatest improvement in both active treatment groups were the 2 items in the hair loss subscale ('Scalp hair loss' and 'Body or eyelashes hair loss', mean changes: À2.3 to À3.7), which reflects the significant clinician-assessed hair regrowth previously reported.…”
Section: Discussionmentioning
confidence: 99%